Object Recognition Memory: Distinct Yet Complementary Roles of the Mouse CA1 and Perirhinal Cortex - Cinalli Jr., David A.; Cohen, Sarah J.; Guthrie, Kathleen; Stackman Jr., Robert W. (Frontiers in Molecular Neuroscience, 2020)
While the essential contribution of the rodent hippocampus to spatial memory is well established, object recognition memory has been traditionally attributed to the perirhinal cortex (PRh). However, results of several studies indicate that under specific procedural conditions, temporary or permanent lesions of the hippocampus affect object memory processes as measured in the Spontaneous Object Recognition (SOR) task. The PRh and hippocampus are considered to contribute distinctly to object recognition memory based on memory strength. Allowing mice more, or less, exploration of novel objects during the encoding phase of the task (i.e., sample session), yields stronger, or weaker, object memory, respectively. The current studies employed temporary local inactivation and immunohistochemistry to determine the differential contributions of PRh and CA1 neuronal activity to strong and weak object memory. Temporary inactivation of the CA1 region of hippocampus immediately after the sample session impaired strong object memory, but spared weak object memory; while temporary inactivation of PRh post-sample impaired weak object memory but spared strong object memory. Additionally, mRNA transcription and translation for protein synthesis are required for the consolidation of episodic memory, and activation patterns of immediate early genes, such as c-fos and Arc, have been linked to behaviorally-triggered neuronal activation and synaptic plasticity. Analyses of c-Fos and Arc protein expression in PRh and CA1 neurons by immunohistochemistry, and of Arc mRNA by qPCR after distinct stages of SOR provide additional support that strong object memory is dependent on CA1 neuronal activity, while weak object memory depends on PRh neuronal activity. Taken together, the results support the view that both PRh and CA1 are required for object memory under distinct conditions. Specifically, our results are consistent with a model that as the mouse begins to explore a novel object, information about it accumulates within PRh, and a weak memory of the object is encoded. If object exploration continues beyond some threshold, a strong memory for the event of object exploration is encoded; the consolidation of which is CA1-dependent. These data serve to reconcile the dissension in the literature by demonstrating functional and complementary roles for CA1 and PRh neurons in rodent object memory.